Spontaneus rupture of renal cell carcinoma in anuric patient on automated peritoneal dialysis - Stojšić Vuksanović, Tatjana S; Knežević, Violeta (Vojnosanitetski pregled, 2021)
Abstract Introduction. Spontaneous subcapsular or perirenal hematomas are relatively uncommon but often diagnostically challenging conditions. We present the first case described in the literature of successful continuation of the full regimen of peritoneal dialysis, that started immediately after urgent nephrectomy due to the spontaneous rupture of kidney cancer. Case report. A 55-year- old man had received continuous ambulatory peritoneal dialysis during 5 years for end-stage renal disease secondary to hypertensive nephropathy. He was switched to automated peritoneal dialysis two months before sudden worsening of his health condition, which was presented with strong left flank pain. Abdominal contrast enhanced computed tomography raised suspicion on retroperitoneal hematoma. The patient underwent radical left nephrectomy and restarted peritoneal dialysis immediately after surgery. The patient was discharged 5 days after the operation without any complications. The pathology report showed papillary renal cell carcinoma. Conclusion. Although renal cell carcinoma is the most common malignant tumor of the kidney, it has been rarely presented with spontaneous subcapsular or perirenal hematomas. However, radical nephrectomy with retroperitoneal approach is a requirement for minimising damage as well as keeping peritoneum integrity, allowing the continuation of automated peritoneal dialysis immediately after surgery without complications.
Keywords: peritoneal dialysis; rupture, spontaneous; kidney neoplasms; nephrectomy